A novel RT‐qPCR assay for quantification of the MLL‐MLLT3 fusion transcript in acute myeloid leukaemia. (1st October 2013) - Abildgaard, Lotte; Ommen, Hans Beier; Lausen, Birgitte; Hasle, Henrik; Nyvold, Charlotte Guldborg
Abstract Objectives Patients with acute myeloid leukaemia (AML) of the monocytic lineage often lack molecular markers for minimal residual disease (MRD) monitoring. The MLL‐MLLT3 fusion transcript found in patients with AML harbouring t(9;11) is amenable to RT‐qPCR quantification but because of the heterogeneity of translocation break points, the MLL‐MLLT3 fusion gene is a challenging target. We hypothesised that MRD monitoring using MLL‐MLLT3 as a RT‐qPCR marker is feasible in the majority of patients with t(9;11)‐positive AML. Methods Using a locked nucleic acid probe, we developed a sensitive RT‐qPCR assay for quantification of the most common break point region of the MLL‐MLLT3 fusion gene. Five paediatric patients with t(9;11)‐positive AML were monitored using the MLL‐MLLT3 assay. Results A total of 43 bone marrow (BM) and 52 Peripheral blood (PB) samples were collected from diagnosis until follow‐up. Two patients relapsed, and both were MRD positive in BM after first induction course. A total of three relapses occurred, and they were detected by RT‐qPCR 3 wks before haematological relapse was diagnosed. Conclusion This MLL‐MLLT3 RT‐qPCR assay could be useful in MRD monitoring of a group of patients with AML who often lack reliable MRD markers.